Partnerships for Knowledge Building: An Emerging Model - Thérèse Laferrière; Mireia Montane; Begona Gros; Isabel Alvarez; Merce Bernaus; Alain Breuleux; Stéphane Allaire; Christine Hamel; Mary Lamon (The Canadian Network for Innovation in Education (CNIE), 2010)
Knowledge Building is approached in this study from an organizational perspective, with a focus on the nature of school-university-government partnerships to support research-based educational innovation. The paper starts with an overview of what is known about effective partnerships and elaborates a conceptual framework for Knowledge Building partnerships based on a review of literature and two case studies of school-university-government partnerships. In one case, a Ministry of Education wanted to bring more vitality into schools of small remote villages, and in the other case another Ministry of Education wanted to renew its school-based international cooperation profile. Emerging from this work is a three-component model for going to scale with Knowledge Building partnerships: Knowledge Building as a shared vision; symmetric knowledge advancement; and multi-level, research-based innovation. Characteristics of, and conditions for, effective partnerships for Knowledge Building are elaborated, and an emerging model is developed to help communities establish effective partnerships and contribute to this evolving model.